2013
DOI: 10.1183/09031936.00027913
|View full text |Cite
|
Sign up to set email alerts
|

Neglected evidence in idiopathic pulmonary fibrosis: from history to earlier diagnosis

Abstract: This perspective highlights some evidence that has hitherto been neglected, especially because it may not have been sufficiently explicated in the clinical respiratory medicine literature. Idiopathic pulmonary fibrosis (IPF) has appeared only in the second half of the 20th century and, like lung cancer and chronic obstructive pulmonary disease, may be a direct consequence of the cigarette smoking epidemic. It is a disease of lung ageing, with most affected patients being .70 years of age. The relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 99 publications
0
40
0
4
Order By: Relevance
“…Although most hot topics in IPF will be reviewed in this series, some other important aspects can be found elsewhere, including the development of biomarkers [42,43], the impact of comorbidities including emphysema (syndrome of combined pulmonary fibrosis and emphysema) [44], gastroesophageal reflux [45,46], lung cancer [47], sleep apnea, cardiovascular disease and diabetes mellitus [48], the increasing role of genetics in the pathogenesis and management of IPF [49,50], comprehensive management and supportive care [51,52], or possible approaches for earlier diagnosis and treatment [53]. We hope readers will enjoy this series on IPF, and that it will translate into better care for IPF patients.…”
Section: Tablementioning
confidence: 99%
“…Although most hot topics in IPF will be reviewed in this series, some other important aspects can be found elsewhere, including the development of biomarkers [42,43], the impact of comorbidities including emphysema (syndrome of combined pulmonary fibrosis and emphysema) [44], gastroesophageal reflux [45,46], lung cancer [47], sleep apnea, cardiovascular disease and diabetes mellitus [48], the increasing role of genetics in the pathogenesis and management of IPF [49,50], comprehensive management and supportive care [51,52], or possible approaches for earlier diagnosis and treatment [53]. We hope readers will enjoy this series on IPF, and that it will translate into better care for IPF patients.…”
Section: Tablementioning
confidence: 99%
“…Epidemiological studies have showed that IPF is more common than previously appreciated in the elderly population [3], with rising prevalence and mortality [4,5]. The role of tobacco smoking is better appreciated [6]. The underlying genetic predisposition to IPF is progressively unveiled [7].…”
mentioning
confidence: 99%
“…IPF predominantly affects elderly male smokers/ex-smokers with a median age at diagnosis of 65-70 years [3]. Although it is a rare disease, with an estimated prevalence range of 1-23 cases per 100 000 European persons [4][5][6][7][8][9], IPF represents a considerable challenge for clinicians.…”
Section: Introductionmentioning
confidence: 99%